WATER QUALITY DYNAMICS IN MILKFISH PONDS WITH WATER SOURCE FROM WASTEWATER OF VANAME SHRIMP CULTURE - Arfiati, Diana; Safara, Raisa; Khofiffah, Agnes (Program Studi Budidaya Perairan Universitas Mataram, 2022)
Wastewater from vaname shrimp culture with a semi biofloc system, was used for milkfish cultivation without additional feed. Fish seeds are stocked 4000 with 18 days of age. The Milkfish pond is 2000 m2, the water level is 0,7 m. Water quality was observed 2 months cultivation. Water samples were taken everyweeks around 9 am, from March to April 2022. During the research, temperature, brightness, pH, dissolved oxygen, CO2 and salinity were relatively stable, except for nitrate and phosphate levels. First observation the levels of nitrate were 0,059 mg/l and phosphate was 0,064 mg/l. When the fish were 2,5 months, nitrate levels increased by 425,4% to 0,31 mg/l and phosphate increased by 479,7% to 0,371 mg/l. This increase is thought the addition of residual water from vannamei shrimp cultivation, so that the pond water level becomes 80 cm. Observation of milkfish at the age of 3 months, nitrate levels decreased 42,6% to 0,178 mg/l and phosphate decreased 8,4% to 0,34 mg/l. This decreasing is thought because nitrate and phosphate are used as a source of nutrients for phytoplankton. The milkfish are 3,5 months, the nitrate level decreases by 58,4% to 0,074 mg/l, but the phosphate level increases by 8,24% to 0,368 mg/l. The increase in phosphate is thought to be from the decomposition of fish feces. And the decreasing of nitrate because used as a source of nutrients for phytoplankton. Water quality monitoring must be carried out regularly, to preserve pond water quality.